Classification, Identification, and Clinical Significance of Proteus, Providencia, and Morganella - O'Hara, Caroline Mohr (American Society for Microbiology, 2000)
This review presents the current taxonomy of the genera Proteus, Providencia, and Morganella, along with the current methods for the identification of each species within the three genera, incorporating both conventional biochemical and commercial methods. While all of these organisms are ubiquitous in the environment, individual case reports and nosocomial outbreak reports that demonstrate their ability to cause major infectious disease problems are presented. Lastly, anticipated antimicrobial susceptibility patterns are reviewed. Many of these organisms are easily controlled, but the advent of newer and more powerful antimicrobial agents has led to some problems of which laboratorians need to be aware.